2015
DOI: 10.1002/psc.2770
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a linear inactive analog of human β-defensin 4 to generate peptides with potent antimicrobial activity

Abstract: Human β-defensins (HBDs) are cationic antimicrobial peptides constrained by three disulfide bridges. They have diverse range of functions in the innate immune response. It is of interest to investigate whether linear analogs of defensins can be generated, which possess antimicrobial activity. In this study, we have designed linear peptides with potent antimicrobial activity from an inactive peptide spanning the N-terminus of HBD4. Our results show that l-arginine to d-arginine substitution imparts considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
(64 reference statements)
2
18
0
Order By: Relevance
“…Although fatty acylation improved antibacterial activity, myristoylated peptides showed potent hemolytic activity unlike the myristoylated analogs of HBD4 [54]. However lauryl peptides were not hemolytic.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although fatty acylation improved antibacterial activity, myristoylated peptides showed potent hemolytic activity unlike the myristoylated analogs of HBD4 [54]. However lauryl peptides were not hemolytic.…”
Section: Discussionmentioning
confidence: 94%
“…walls [66]. It appears that binding and destabilization of outer membrane of Gram-negative bacteria is an essential step for the activity of HD5 and analogs [54]. Efficient interaction with bacterial surfaces enhances the antibacterial activity of defensin derived peptides.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, Alves et al ., have reported a correlation between extent of surface charge neutralizing ability and minimum inhibitory concentrations for amphipathic CAMPs [50]. We have previously shown that effective interaction of human defensin analogs with bacterial surfaces enhances antibacterial potency [39, 51, 52]. With a view to understand, how human defensins vary in their ability to interact with bacterial surfaces, we compared the extent of electrostatic interactions between the E .…”
Section: Resultsmentioning
confidence: 99%
“…2013; Wood et al. 2013; Mathew and Nagaraj 2015a,b; Olli, Nagaraj and Motukupally 2015; Sharma, Mathew and Nagaraj 2015; Tripathi et al. 2015).…”
Section: Introductionmentioning
confidence: 99%